Strategi Meningkatkan Kecerdasan Emosional dan Spiritual Siswa - Abdul Qadir Jaelani; Lailul Ilham (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
Based on eight educational standards in the national education law and based on the tendency of educational institutions to be more oriented towards increasing intellectual intelligence of students while increasing emotional and spiritual intelligence is relatively not a priority, even though these aspects are important parts that must be improved in students. The study was conducted to find out the counseling strategies of the BK in improving the emotional and spiritual intelligence (ESQ) of MTs Negeri 3 Mataram students. This study uses a qualitative-descriptive approach, the data collection techniques in the form of observation, interview, and documentation. The research subjects are the BK teacher, homeroom teacher, and school administration teacher (TU). Field results indicate that the strategies used by counselors in improving the emotional and spiritual intelligence (ESQ) of MTs Negeri 3 Mataram students with three program qualifications, including: 1) Teaching and Learning Activities, they are: (a) Addition of religious subjects, (b) addition of lessons in moral aqeedah, (c) recitation of prayers before and after learning; 2) Ubudiyah's activities include: (a) duha prayer in congregation, (b) short surah readings, (c) religious tourism; 3) Sosial Activities, including: (a) compensation for orphans, (b) sharing with the poor, (c) sosial services. Berdasarkan delapan standar pendidikan dalam undang-undang pendidikan nasional serta berdasarkan kecenderungan lembaga pendidikan yang lebih berorientasi pada peningkatan kecerdasan intelektual siswa sementara peningkatan kecerdasan emosional dan spiritual relatif tidak menjadi prioritas, padahal aspek tersebut merupakan bagian penting yang mesti ditingkatkan dalam diri siswa. Penelitian dilakukan untuk mengetahui strategi guru BK dalam meningkatkan kecerdasan emosional dan spiritual (ESQ) siswa MTs. Negeri 3 Mataram. Penelitian ini menggunakan pendekatan kualitatifhttpdeskriptif, dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Subjek penelitiannaya adalah guru BK, wali kelas, dan guru bidang tata usaha (TU) sekolah. Hasil lapangan menunjukkan bahwa strategi yang digunakan guru BK dalam meningkatkan kecerdasar emosional dan spiritual (ESQ) siswa MTs. Negeri 3 Mataram dengan tiga kualifikasi program, antara lain: 1) Kegiatan Belajar Mengajar, terdapat: (a) Penambahan mata pelajaran agama, (b) penambahan pelajaran aqidah akhlak, (c) pembacaan doa setiap sebelum dan setelah pembelajaran; 2) Kegiatan Ubudiyah, terdapat: (a) sholat duha berjamaah, (b) pembacaan sutrat-surat pendek, (c) wisata religi; 3) Kegiatan Sosial, meliputi: (a) santunan anak yatim, (b) berbagi kepada kaum miskin, (c) bakti sosial.